Coexistence of Pelviureteric Junction Obstruction and Vesicoureteral Reflux (Medicine Today, 2021)
Introduction: The most common upper urinary tract problem in children is obstruction at the pelviureteric junction. It happens with varying degrees of seriousness. Ultrasonography and DTPA (Diethylene Triamine Penta-acitic Acid) renography are commonly used to detect it. Objective: To find out the coexistence of ipsilateralpelviureteric junction obstruction with vesicourenteral reflux.Materials and Methods: This prospective study was conducted in the Department of Paediatric Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January 2006 to May 2007 over a period of 1 year 5 months. Thirty-five patients with unilateral hydronephrosis due to PUJ obstruction were included in this study (age: 1 month-15 years). Results were analyzed using Statistical Package for Social Science (SPSS).Results: Incidence of Vesicoureteral reflux (VUR) among pelviureteric junction (PUJ) obstruction patients was 8.6%. Of them Grade-I VUR was 33.3% and grade-II VUR was 66.7%. Mean age of the patients was 4.71 ± 1.97 years and with VUR was 9.33 ± 4.93 years. Male to female ratio was 4:1. Only 5.7% mothers had regular antenatal checkup and 28.5% had irregular. Majority of the patients 28 (80%) were presented with painless loin mass, 6 (17.1%) with fever, 8 (22.9%) with loin pain and 8 (22.9%) with failure to thrive. Three patients (8.6%) showed abnormal R/M/E and all of the abnormal R/M/E samples showed positive culture.Conclusions: Incidence of Vesicoureteral reflux (VUR) among pelviureteric junction (PUJ) obstruction patients was 8.6%.Medicine Today 2021 Vol.33(2): 94-97